Drug efficacy of ivermectin against primary nematodes parasitizing captive Przewalski’s horse (Equus ferus przewalskii) after ten years of annually treatment - Tang L.; Xiu Y.; Yan L.; Cui Y.; Ma X.; Ente M.; Zhang Y.; Li K.; Zhang D. (Helminthologia, 2020)
Reintroduction of endangered species to natural habitat is considered as an important tool for conservation. The effect of drug management on captive population of reintroduced species is largely neglected. Decreased drug efficacy could pose a substantial threat to health of animals. More importantly, captive population without proper drug administration could act as transmission medium of resistance nematodes to wild population, making it important to delay the occurrence of drug resistance in captive population. Ivermectin have been used in captive Przewalski’s horse (Equus ferus przewalskii) to eradicate intestinal parasitic nematodes annually, while no available studies describing the drug efficacy in the recent ten years. Here, fecal egg counts pre- and post-treatment were performed with ivermectin through individual trace. Both large and small strongyles were identifi ed by larval culture. The fecal egg count reduction was almost 100% based on egg counting data of 448 samples from 13 Przewalski’s horses. Feces of two Przewalski’s horses were sampled for successive 20 days. Eggs per gram feces usually increased dramatically at the period of 1 – 2 post-treatment days and declined persistently to 0.0 within 15 days. A sustained high ivermectin efficacy against neither Parascaris equorum nor strongyles was indicated, which can be partly explained by the low deworm frequency.